2022
DOI: 10.1111/acel.13761
|View full text |Cite
|
Sign up to set email alerts
|

P2Y6 receptor‐dependent microglial phagocytosis of synapses mediates synaptic and memory loss in aging

Abstract: Aging causes loss of brain synapses and memory, and microglial phagocytosis of synapses may contribute to this loss. Stressed neurons can release the nucleotide UTP, which is rapidly converted into UDP, that in turn activates the P2Y 6 receptor (P2Y 6 R) on the surface of microglia, inducing microglial phagocytosis of neurons. However, whether the activation of P2Y 6 R affects microglial phagocytosis of synapses is unknown. We show here that inactivation of P2Y 6 R decreases microglial phagocytosis of isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 65 publications
0
28
0
Order By: Relevance
“…Similar effects were seen for C2 and the complement receptors CR1 and C1QR1/CD93 in R47H/+ microglia, though these genes were not as highly expressed (Figure 5k). Furthermore, the purinergic receptor P2RY6, which mediates synapse loss in aging, was also upregulated in microglia carrying TREM2 mutations (Figure S3A; Dundee et al, 2023). Thus, these observations indicate that TREM2 R47H/+ microglia can promote synapse loss in vivo, likely mediated by some combination of inflammatory mechanisms, increased P2RY6 signaling, and/or activation of complement‐dependent synaptic pruning.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Similar effects were seen for C2 and the complement receptors CR1 and C1QR1/CD93 in R47H/+ microglia, though these genes were not as highly expressed (Figure 5k). Furthermore, the purinergic receptor P2RY6, which mediates synapse loss in aging, was also upregulated in microglia carrying TREM2 mutations (Figure S3A; Dundee et al, 2023). Thus, these observations indicate that TREM2 R47H/+ microglia can promote synapse loss in vivo, likely mediated by some combination of inflammatory mechanisms, increased P2RY6 signaling, and/or activation of complement‐dependent synaptic pruning.…”
Section: Resultsmentioning
confidence: 97%
“…This difference between our in vitro and in vivo results likely reflects the distinct mechanisms that govern synapse loss in vivo (Hammond et al, 2019). Inflammatory insults, activation of uridine signaling, and complement system activation are all associated with synapse loss in the mouse brain (Dundee et al, 2023; Propson et al, 2021; Rao et al, 2012). In addition to the proinflammatory effect that TREM2 R47H/+ mutations confer on microglia (Figures 1 and 2), our original RNA sequencing experiments also indicated an upregulation of multiple complement pathway components in R47H/+ microglia (Figure 5j).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5G). We chose this receptor since it was shown that upregulation of the P2Y6 receptor in response to damaged neurons and synapses triggers an increase in microglial phagocytosis (Dundee et al 2023, Koizumi et al 2007. P2Y6 is not considered as a chemotactic receptor (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Microglial phagocytosis is regulated by several factors, including the microglial P2Y 6 receptor (P2Y 6 R) activated by extracellular UDP (uridine diphosphate) [ 5 , 6 ]. We recently reported that microglial phagocytosis of synapses during aging is mediated by P2Y 6 R [ 7 ]. Inhibition or knockout of P2Y 6 R reduced microglial phagocytosis of synapses and synaptic loss in co-cultures of neurons and microglia.…”
mentioning
confidence: 99%